Comparison of Legal Protection of Telemedicine Services in Indonesia and Malaysia - Nasir, Citra; Ichsan, Nursyamsi; Attas, Nasrah Hasmiati (IJBLE Scientific Publications Community Inc., 2022)
The purpose of this study is to compare the legal protection of telemedicine in Indonesia and Malaysia. The research method uses normative legal research using a statutory approach and concept approach. The results of the study obtained the conclusion that the results of the study obtained the conclusion that health services through telemedicine have a greater risk than health services through face-to-face or in person, for example in terms of diagnosis the doctor will be better and more precise if done directly between the doctor and the patient. In Indonesia and Malaysia, each has regulations to provide legal protection for patients in telemedicine services as well as for telemedicine service providers. The implementation of telemedicine services in Indonesia by health facilities while Malaysia directly by hospitals in coordination with clinics and health centres because doctors can only conduct virtual consultations with people who are already patients this can be seen as a continuation of care.